In situ prediction of phenolic compounds in puff dried Ziziphus jujuba Mill. using hand-held spectral analytical system. (30th November 2020) - Arslan, Muhammad; Xiaobo, Zou; Shi, Jiyong; Elrasheid Tahir, Haroon; Zareef, Muhammad; Rakha, Allah; Bilal, Muhammad
Highlights: Z. Jujuba samples were dried by mean of puff drying system. Hand-held spectral analytical system was used for acquisition of spectral information. Prediction stability of build models were improved with variable selection algorithms. Si-ACO-PLS was most reliable for quantification of phenolic compounds. Abstract: A low cost hand-held spectral analytical system was developed for in situ screening of phenolics and flavonoids in puff dried Ziziphus jujuba ( Z. Jujuba ) samples. Standards of gallic acid, caffeic acid, l -epicatechin, phloridzin and cianidanol were used to quantify the individual phenolics and flavonoids using high performance liquid chromatography-diode array detector (HPLC-DAD). The synergy interval partial least square with ant colony optimization (Si-ACO-PLS) was attempted to optimize and capture informative variables for the prediction of target compounds. The model performance was evaluated using correlation coefficients of prediction (Rp); root mean square error of prediction (RMSEP) and residual predictive deviation (RPD). The Si-ACO-PLS yielded optimal performance, 0.8540 ≤ Rc ≤ 0.9250, 0.8360 ≤ Rp ≤ 0.9056, 0.84 ≤ RMSEP ≤ 16.30 and 2.03 ≤ RPD ≤ 2.26. The hand-held spectral analytical system coupled with Si-ACO-PLS proved to the reliable, rapid and cost-effective method to quantify the phenolics and flavonoids in Z. Jujuba .